Chapter 4: Guidelines for the diagnosis and treatment of overactive bladder (OAB) and neurogenic detrusor overactivity (NDO). Issue 3 (July 2014) - Nambiar, Arjun; Lucas, Malcolm
Abstract This chapter focuses on the position of botulinum toxin type A in the treatment pathway for overactive bladder (OAB) and neurogenic lower urinary tract dysfunction associated with neurogenic detrusor overactivity (NDO), and the recommendations of the major international guideline groups. Recommendations of different guideline groups may vary, especially when evidence is weak, often because of differences in methodology and panel composition. Relevant guidelines from the European Association of Urology, American Urological Association, and the UK National Institute for Care and Clinical Excellence were reviewed, and the recommendations that form the basis of the treatment algorithms have been discussed. Any differences between guidelines have been highlighted and special emphasis made on the position of botulinum toxin type A in these pathways. In all the reviewed guidelines, botulinum toxin type A is recommended, alongside sacral nerve neuromodulation, to treat OAB and NDO in patients who have failed oral therapy. The evidence base is consistent, but further evidence is required regarding optimal dosing regimens and injection technique. Neurourol. Urodynam. 33:S21–S25, 2014. © 2014 Wiley Periodicals, Inc.